Effect of Right Median Nerve Stimulation on Clinical Efficacy and Prognosis of Patients with Consciousness Disorder Caused by Traumatic Brain Injury - Kun ZHAO; Aixian LIU (康复学报)
Objective:To investigate the clinical effect of right median nerve stimulation on consciousness disorder caused by traumatic brain injury and its influence on prognosis.Methods:A total of 92 patients were divided into control group and experimental group according to random number table method, with 46 cases in each group. The control group was given conventional wake-up promotion therapy, while the experimental group was given right median nerve stimulation therapy on the basis of that in the control group. The levels of neurotransmitters, cerebral hemodynamics, clinical scores, adverse reactions and prognosis before and after treatment were compared between the two groups.Results:Before treatment, there was no significant difference in neurotransmitter level, cerebral hemodynamics and clinical score between the two groups (P>0.05). After treatment, norepinephrine (NE), dopamine (DA), mean blood flow velocity (VM), blood flow velocity (VS), electroencephalogram (EEG) score, auditory brainstem response (ABR), and Glasgow Coma Scale (GCS) increased in both groups (P<0.05), and the above indexes in the experimental group were higher than those in the control group (P<0.05). The β-endorphin (β-EP) and pulsatility index (PI) of the two groups decreased (P<0.05), while that of the experimental group was lower than that of the control group, with statistically significant difference (P<0.05). There was no significant difference in the incidence of adverse reactions between the two groups (P>0.05). The prognosis of the experimental group was better than that of the control group (P<0.05).Conclusion:Right median nerve stimulation has a positive wake-up promoting effect on patients with consciousness disorders caused by traumatic brain injury. It can regulate neurotransmitter release, improve cerebral blood flow and brain electrical activity, and reduce disability rate.